Neogene and Pleistocene geodynamics: the paleoseismic evolution of Armorica (Western France) - Van Vliet-Lanoë, Brigitte; Authemayou, Christine; Le Roy, Pascal; Renouf, John C.; Combes, Philippe; Ego, Frederic (Frontiers in Earth Science, 2024)
The evolution of the passive Armorican margin during the Neogene and Quaternary was analyzed using field data. The morphology of the margin attests to a late Hercynian shaping, further deformation during the Mesozoic mid-Atlantic opening and the Alpine Orogeny, and ultimately a Late Cenozoic uplift, mostly related to an onshore isostatic accommodation in response to erosion and limited tectonic activity. A very limited strike-slip dynamic, with very low seismicity, accommodated the Neogene-Pleistocene N170 strains around the rigid Armorican terrane. South Armorican and English Channel shear zones adjusted the Alpine convergence, facilitating its transpressive slip to the west. Permo-Triassic N150 faults were reactivated during the inversion phases that began after the Bartonian under the distal control of the Alpine convergence and the decrease in the Atlantic spreading rate after 34 Ma. The Armorican marine platforms were stable after the late Eocene and slightly subsident, experiencing pulsed episodes of transient lithospheric doming during the Neogene and Quaternary. Coseismic activity onshore without surface rupture was recorded around ~5.3, ~3.7, ~2.4-1.2 Ma, and ~400-250 ka, in tandem with an inland exhumation driven by isostatic adjustment due to an intensification of periglacial erosion at the onset of the early interstadials or by agriculture. Low-magnitude and ubiquitous shallow seismic activity seems related today to an isostatic uplifted old brittle-ductile transition due to the accumulation of shearing strain.